(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This article presents the main challenges of the Mozambican Hospital Administrator. To this end, the research was of a qualitative, exploratory and descriptive nature, which, through bibliographical research, sought to identify and understand what may constitute challenges for the Mozambican hospital administrator in a context, not only due to technological developments that are constantly being updated, but also due to the multi-professional understanding of the health sector, which tends to be increasingly professional. Challenges for the Mozambican Hospital administrator were identified as those related to the inabilities of the Mozambican Ministry of Health and its levels of administrative and technical attention in affecting HR graduates in AGH in subsidy of top structures; the non-application of the 2025 agenda and its subsequent review that could encompass better strategies for the placement and insertion of AGH. In the form of strategic recommendations, the study emphasizes the need for government institutions and other interested agencies to prioritize the allocation of Hospital Administrators within hierarchical structures, and other professional care classes within care structures.